HUBUNGAN DAYA TAHAN OTOT LENGAN DENGAN KEMAMPUAN PUKULAN LURUS PADA OLAHRAGA BELA DIRI PENCAK SILAT SISWA SMA NEGRI 1 KABAWO - Wa Fina; Saifu; Muhammad Rusli (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the relationship between arm muscle endurance and the ability to punch straight in pencak silat SMA Negri 1 Kabawo students.the population in this study were all male students who took part in the extracurricular activities of SMA Negri 1 Kabawo students, totaling 35 people. The sampling technique was carried out with a total sampling technique of 35 people and was used as the sample of this study. The research instrument used to measure arm muscle endurance is to use a push-up test until the teste can no longer do up and down push-up movements and a straight punch ability test for 30 seconds. The data of this study were analyzed by statistical technique of product moment correlation with a significant level of 0.05 or 5%. The results of this study indicate that there is a significant relationship between arm muscle endurance and straight punch ability in pencak silat martial arts. Where (rxy) = 0.596 >r table (0.05:35) = 0.334 with a coefficient of determination =0.36 or 36%. Thus, arm muscle endurance contributes to the straight stroke ability of pencak silat martial arts in SMA Negri 1 Kabawo students. Based on this analysis, it can be concluded that the better the arm muscle endurance of SMA Negri 1 Kabawo students, the better the straight hitting ability